Analisis Efektivitas Sumber Pendapatan dan Belanja Pada Anggaran Pendapatan dan Belanja Desa di Desa Lopak Aur Kecamatan Pemayung - Evi Fauzani; Etty Siswati; Fajar Hamami (CITRA EKONOMI, 2022)
The Village Revenue and Expenditure Budget (APBDesa) is a village goverment budget that is realized the form of number, in essence the APBDesa is an annual program. The Village Revenue and Expenditure Budget (APBDesa) must be used as possible for the prosperity of the village community.In terms of village finance and assets, there are two things that need serious attention from the village, namely village income and village expenditure. Village income comes from various sources of income found in the village and village income is used by the village to finance various types of village expenditure where village expenditure is prioritized to meet the development needs agreed upon in village meetings.Researchers chose Lopak Aur village because if the village’s income source rose, it would be followed by an increase in village expenditure, whereas if the village’s income source declined, it would also be followed by a decrease in village expenditure.So the result of this study are: It can be seen that income from 2019 to 2020 has increased as well as shopping for the Lopak Aur village has increased in doing the shopping it self. In the proportion of both income and expenditure it self, 2019 is a higher proportion than in 2020